Russia as the master shaper of the Arctic - Volšanská, Jana; Machoň, Miloslav, 1988-; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The thesis deals with the position of the Russian Federation as the shaper of the Arctic region. The analysis is based on theoretical methodology concerning the concept of actorship, shaper definition, narratives and foreign policy. Lastly, the thesis will focus on the connection between the aged narratives and the Arctic strategies of the Russian Federation.
Vedoucí práce: Miloslav Machoň
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses